2022
DOI: 10.1007/s40265-022-01785-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroids in Adults with Non-cystic Fibrosis Bronchiectasis: From Bench to Bedside. A Narrative Review

Abstract: Due to their potent anti-inflammatory capacity (particularly in predominantly eosinophilic inflammation) and immunosuppressive properties, inhaled corticosteroids (ICSs) are widely used in asthmatic patients and also in individuals with chronic obstructive pulmonary disease (COPD) who suffer multiple exacerbations or have peripheral eosinophilia. However, there is little evidence for their use in non-cystic fibrosis bronchiectasis (hereafter, bronchiectasis). According to data extracted from large databases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 132 publications
0
13
0
1
Order By: Relevance
“…Further studies may be useful to investigate the beneficial effects of therapeutic modalities such as inhaled antibiotics, including N- Acetylcysteine in Indigenous patients ( 45 ). Use of ICS among patients with bronchiectasis is controversial ( 46 , 47 ). Nonetheless, in our study more than half of the patients recorded an ICS prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies may be useful to investigate the beneficial effects of therapeutic modalities such as inhaled antibiotics, including N- Acetylcysteine in Indigenous patients ( 45 ). Use of ICS among patients with bronchiectasis is controversial ( 46 , 47 ). Nonetheless, in our study more than half of the patients recorded an ICS prescription.…”
Section: Discussionmentioning
confidence: 99%
“…However, among patients prescribed ICS, we observed a higher proportion had an admission related to ICD code J44 compared to patients with no ICS prescription. Utilisation of ICS among patients with bronchiectasis is controversial and may be detrimental [ 65 ]. Previous studies from our centre had reported higher use of ICS among Indigenous patients with bronchiectasis and to have a significant decline in lung function parameters with ICS [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled corticosteroids must be avoided since they can increase the frequency of exacerbations and the risk of mycobacterial diseases. 41 , 42 However, following the recommendations applied to noncystic bronchiectasis, in cases of PTLD associated with asthma, inhaled corticosteroid therapy may be justified. 24 Similarly, for chronic inflammation in patients with noncystic fibrosis bronchiectasis, the use of macrolides is recommended for a minimum period of 6-12 months in patients with bronchiectasis and at least two exacerbations per year.…”
Section: Management Of Ptldmentioning
confidence: 99%